2020
DOI: 10.1016/j.mayocpiqo.2020.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Status of Acute Myocardial Infarction in Southern India During COVID-19 Lockdown: A Multicentric Study

Abstract: There has been a reduction in the reported cases of acute myocardial infarction (MI) across the globe during the outbreak of coronavirus disease 2019 (COVID-19) (severe acute respiratory distress syndrome coronavirus 2). An attempt was made to find out the number of acute MI cases treated during the COVID-19 lockdown period (April 2020) and highlight the possible reasons for the changes in the occurrence. A multicentric retrospective observational study was performed to collect the selected data from 12 privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Several centres have reported a decrease in admissions during the pandemic, 1,2,6 whereas others have found no significant difference compared with pre-COVID-19 levels. 5 With regard to the type of MI, most studies have shown a decrease in NSTEMI admissions during the COVID-19 pandemic, but mixed results pertaining to STEMI presentations.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Several centres have reported a decrease in admissions during the pandemic, 1,2,6 whereas others have found no significant difference compared with pre-COVID-19 levels. 5 With regard to the type of MI, most studies have shown a decrease in NSTEMI admissions during the COVID-19 pandemic, but mixed results pertaining to STEMI presentations.…”
Section: Discussionmentioning
confidence: 95%
“…Beyond an immediate impact on mortality and morbidity, this pandemic has also had secondary ramifications for the provision of healthcare as hospitals change existing workflows to accommodate the screening and treatment of COVID and governments impose lockdown measures that directly and indirectly affect patients' presentation to hospitals.Studies have been published about the effect of the COVID-19 pandemic on procedural volumes of elective percutaneous coronary intervention (PCI), as well as on the presentations and outcomes of acute MI (AMI). [1][2][3][4][5] Many of these studies only capture the perspective of a single centre in a particular country. Furthermore, study findings are mixed, with some studies reporting a decrease in non-ST segment elevation MI (NSTEMI) or ST-elevation MI (STEMI) presentations since the onset of the pandemic, and others finding no significant difference, particularly in the STEMI caseload.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…During the COVID-19 pandemic, several studies reported a decrease in the incidence of hospitalization for acute myocardial infarction worldwide. [43][44][45][46][47][48][49] Among patients with non-ST segment elevation myocardial infarction (NSTEMI) and STEMI, Solomon et al noticed a decline by up to 48% in the weekly rates in March and April 2020 in northern California compared with the same week in 2019. 43 44 The ongoing French Cohort of Myocardial Infarction Evaluation (FRENCHIE) registry, in which 21 centers participated, was recently analyzed by Mesnier et al According to their findings, admissions for acute myocardial infarction decreased by 30% from 686 to 481 between 4 weeks prior to and 4 weeks after the lockdown.…”
Section: Potential Mechanisms Of Covid-19-associated Myocardial Injurymentioning
confidence: 99%